Dehydration of mammalian erythrocytes affects their sensitivity to mechanical stress - Shpakova, Nataliya M.; Orlova, Nataliya V.; Nipot, Elena Ye. (Problems of Cryobiology and Cryomedicine, 2015)
Sensitivity of human, bovine, rat and equine erythrocytes to effect of mechanical stress in the media containing 0.15, 0.4 and 0.6 mol/l NaCl was studied. Mechanical stress of mammalian erythrocytes in the medium containing 0.15 mol/l NaCl results to the loss of K+ by cells: from 30% for equine erythrocytes and 60% for bovine cells. Bovine and equine erythrocytes in the medium, containing 0.15 mol/l NaCl show a maximum resistance on hemolysis index to mechanical stress effect. It has been shown that dehydration of human, bovine, rat, and equine erythrocytes in the media with 0.4 and 0.6 mol/l NaCl increases sensitivity of cells to mechanical stress. Bovine and rat erythrocytes are the most sensitive to an increase in osmotic load under mechanical stress on hemolytic damage index, and equine cells are the most sensitive to potassium ion outflux index. Different sensitivity of mammalian erythrocytes to mechanical stress under osmotic load is supposed to be determined by specific peculiarities of water transport and lipid composition of erythrocyte membranes. Comparative analysis of dehydration effect of erythrocytes on their resistance to stress factors showed that formation of stable state of cells (in the medium with 0.4 mol/l NaCl) to hypertonic shock effect did not provide their resistance under mechanical stress. Probl Cryobiol Cryomed 2015; 25(1): 24-32.